MENINGKATKAN HASIL BELAJAR KERJA BANGKU - Sukarjo, Mochammad (Perspektif Ilmu Pendidikan, 2012)
The objective of this research is to determine the relationships between inductive thinking (X1) and student vocational attitude toward technician’s profession (X2) individually and simultanously and learning achievement (Y) in bench work subject. The research conducted in State Vocational High School in East Jakarta, in the school year of 200/2010 proved the positive relationships between the independent variables (X1 and X2, individually and simultanously) and the independent variable (Y). Based on the reseach findings, this research identified some implications and give a number of suggestions to follow up.